BIM in facilities management applications: a case study of a large university complex. Issue 3 (6th July 2015) - Kassem, Mohamad; Kelly, Graham; Dawood, Nashwan; Serginson, Michael; Lockley, Steve
Abstract : Purpose: – Building information modelling (BIM) in facilities management (FM) applications is an emerging area of research based on the theoretical proposition that BIM information, generated and captured during the lifecycle of a facility, can improve its management. Using this proposition as a starting point, the purpose of this paper is to investigate the value of BIM and the challenges affecting its adoption in FM applications. Design/methodology/approach: – Two inter-related research methods are utilised. The literature is utilised to identify the application areas, value and challenges of BIM in FM. Due to the lack of case studies identified in the literature review, and to provide empirical evidence of the value and challenges of BIM in FM, a case study of Northumbria University's city campus, is used to empirically explore the value and challenges of BIM in FM. Findings: – The results demonstrated that BIM value in FM stems from improvement to current manual processes of information handover; improvement to the accuracy of FM data, improvement to the accessibility of FM data and efficiency increase in work order execution. The main challenges were the lack of methodologies that demonstrate the tangible benefits of BIM in FM, the limited knowledge of implementation requirement including BIM for FM modelling requirements, the interoperability between BIM and FM technologies, the presence of disparate operational systems managing the same building and finally, the shortage of BIM skills in the FM industry. Originality/value: – There is lack of real-life cases on BIM in FM especially for existing assets despite new constructions representing only 1-2 per cent of the total building stock in a typical year. The originality of this paper stems from both adding a real-life case study of BIM in FM and providing empirical evidence of both the value and challenges of BIM in FM applications.